Ciclagem de nutrientes em diferentes condições edafoclimáticas em trecho de Floresta Ombrófila Densa - Castro, Kallil Chaves (2018)
In general, the soil receives several influences during the processes of weathering: climate, organisms, landscape and material of origin, that over the time are important factors in it formation. Their interaction with vegetation and climate, and how these factors contribute to the nutrients cycling, give scope for even more elucidative research. In this way, this study aimed to investigate soil formation, nutrient cycling dynamics and the relation in the plant-soil system through microbial activity. The study was carried out in a section of Tropical Montane Rain Forest located in the Caparaó National Park, where seven plots were implanted. For the classification of soils, trenches were opened in seven plots implanted in the study area, and morphological, physical and chemical analyzes were performed for each profile and later classified according to the Brazilian Soil Classification System. Microbiological activity in the surface layer of soils was also studied by enzymatic activity (Urease, ßGlucosity and Phosphatase), microbial biomass, and soil carbon and nitrogen. The study of nutrient cycling was carried out with litterfall and leaf decomposition. The collection and litter were carried out monthly during January 2013 and December 2016. The deposited litter was separated into fraction: Leaves and Other Materials. The deposited litter fractions and the accumulated litter were taken to the laboratory and the chemical analyzes of macronutrients, lignin, cellulose and total polyphenols were performed by season. The litter and the constant and decomposition were correlated with the environmental data. Six different types of soils were classified, distributed in three distinct classes: Latosols, Cambisols and Organosols. The soils were mostly shallow, low fertility and high organic matter content. The production of litter showed to be like the one of the four years of studies, however, the accumulation of litter reduced to the second year. There was a reduction in the contribution of the fractions during autumn and winter, and there was no seasonal difference for the accumulation of biomass. In relation to the contents of C, N, and P, they did not present a marked seasonality for the leaves fraction and the Other 9 Materials Fraction. Higher P contents were observed for the Other Materials Fraction. The content of C varied in accumulated litter, mainly in winter. The total polyphenols content was mainly in the leaves fraction and the C:N, Polyphenols:N, Lignin:N and Lignin + Cellulose:N ratio were positively correlated with the altitudinal gradient. Microbiological activity in the soils was seasonal and influenced by the altitudinal alteration, correlating strongly with carbon and nitrogen in the summer and winter of the superficial layer of the soils. Both the microbiological activity when the carbon and nitrogen contents were correlated mainly with the chemical characteristics of the plant material deposited and accumulated in the study area, indicating a strong relationship between the vegetation and the microbiological community.